Integrating structure and function of tandem-repeat galectins - Troncoso, María Fernanda (2012)
Galectins (GALs) are evolutionarily-conserved lectins defined by at least one carbohydrate recognition domain (CRD) with affinity for beta-galactosides and conserved sequence motifs. Although the biological roles of some members of this family, including the ‘proto-type’ GAL-1 and the ‘chimera-type’ GAL-3 have been widely studied, the functions of ‘tandem-repeat’ galectins are just emerging. The subgroup of ‘tandem-repeat’ galectins (GAL-4, -6, -8, -9, and -12) contain two distinct CRDs, connected by a linker peptide. Here we integrated and distilled the available information on ‘tandem-repeat’ galectins, their specific structures, potential ligands and biological activities in inflammatory and neoplastic diseases. While GAL-4 has been implicated in inflammatory bowel diseases, either as a pro-inflammatory or pro-apoptotic mediator, GAL-8 plays roles in autoimmune diseases such as rheumatoid arthritis and lupus erythematosus and modulates tumor progression. GAL-9 controls allergic inflammation and Th1/Th17-mediated autoimmunity and has prognostic value in certain tumor types. Finally, GAL-12 plays important roles in adipocyte physiology. Although this information is just emerging, further studies are needed to dissect the biological roles of ‘tandem-repeat’ galectins in health and disease.